Paralegal dan Kopi: Sebuah Kombinasi Layanan Konsultasi Hukum dan Coffee Shop di Desa Wanureja Tegal di Era Digital Teknologi: Paralegal and Coffee: A Combination of Legal Consulting Services and Coffee Shop in Wanureja Village, Tegal in the Digital Technology Era - Waspiah, Waspiah; Rodiyah, Rodiyah; Setiawan, Andry; Cahyani, Kartika Fajar; Pertiwi, Adinda Ratna; Bimantara, Bayu (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
The Indonesian people's fondness for coffee has become one of its own potentials and attractions, both in the fields of economy and tourism, as well as socio-cultural. Various coffee shops with various concepts emerged, not only in big cities but also in villages. With the rapid flow of information and technology, it is possible for this business to have sustainability and resilience. In the cultural aspect, this business can survive because of the cultural tendency of the Indonesian people who like to discuss, gather, and talk about many things in various ways. Seeing this potential, the author tries to combine the concept of cultural culture (craving for coffee) with a legal consultation service program by paralegals in Wanureja Village, Tegal Regency, Central Java. This program is a community service program funded by the Faculty of Law, State University of Semarang. This program aims to initiate and develop a legal consultation service center at the village level by utilizing coffee shops as a means of meeting clients with consultants.